Advocating for Fat Activism in a Therapeutic Context. Issue 1 (3rd April 2019) - Matacin, Mala L.; Simone, Melissa
Abstract: Sizeism has a negative impact on women and perpetuates fat shaming. Conventional therapeutic suggestions for addressing weight concerns focus on self-discipline rather than on the larger social, cultural, or political contexts of weight stigma. Feminist scholars, therapists, and activists have encouraged social activism to promote psychological well-being and challenge systemic weight prejudice. Results of research on health prevention and promotion efforts have begun to shift thinking away from weight loss and toward deconstructing and changing anti-fat attitudes. We highlight some individual and community-based fat activists to illustrate how their strategies and ideas challenge sizeism in a variety of areas, including the rhetoric of fat, body positivity, photography/art, nutrition/exercise, and diversity/intersectionality. Fat activism has utility within a therapeutic context, especially for those who have experienced sizeism. We strongly encourage therapists to work closely with clients on finding sources and types of fat activism that represent their unique identities, which may be more difficult for those with marginalized identities.